A method for improving the surface quality of cemented carbide sintered blank
By using gradient gasified dewaxing paraffin molding agent made of a mixture of multiple label paraffin waxes, combined with an optimized dewaxing process, the surface defects of cemented carbide sintered blanks caused by traditional single label paraffin waxes are solved, significantly improving surface quality and product performance.
Patent Information
- Application Number
- CN202411382986.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-09-30
AI Technical Summary
In the production of traditional cemented carbide, the vaporization of single-grade paraffin causes holes and pits to appear on the surface of the sintered blank, affecting the surface quality, subsequent processing and coating performance.
A mixed paraffin molding agent with gradient vaporization dewaxing characteristics is made by mixing a variety of paraffin wax of different labels. Through an optimized gradient dewaxing process, the furnace temperature is controlled to be in the range of 150~500℃ to gradually remove paraffin wax.
It effectively reduces the pore channels generated during the dewaxing process, significantly improves the surface finish of the cemented carbide sintered blank, enhances the coating adhesion, reduces cutting resistance, and improves the overall product quality.
Smart Images

Figure CN118893213B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cemented carbide manufacturing, and in particular relates to a method for improving the surface quality of a cemented carbide sintered blank. Background Art
[0002] Due to its excellent performance of high hardness and high toughness, cemented carbide has been widely used in cutting tools, mining, electronic chip processing and other fields. In the process of cemented carbide production, cemented carbide powder needs to be mixed with a certain amount of forming agent to be pressed into products of various shapes. Paraffin wax is the preferred material for cemented carbide forming agent. It is widely used because of its high purity, easy removal, low residual carbon and good particle stability. In the traditional production of cemented carbide mixtures, a single paraffin wax is usually selected as a forming agent, and then kept at a certain temperature during sintering. Through the gasification of paraffin wax, the "gasification channel" gradually formed from the inside to the surface of the pressed green sheet is removed. However, due to its high content, single composition and fixed gasification temperature, the traditional single-grade paraffin wax gradually evolves into large holes on the surface of the pressed green sheet due to the combined effect of the intense gasification of paraffin wax and capillary force during the paraffin removal stage. After further sintering, obvious defects such as holes and pits appear on the surface of the green sheet, which seriously affects the surface quality of the product and the subsequent processing and coating performance. Summary of the invention
[0003] In order to solve the problems existing in the prior art, the main purpose of the present invention is to provide a method for improving the surface quality of a cemented carbide sintered blank.
[0004] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:
[0005] A method for improving the surface quality of a cemented carbide sintered blank comprises the following steps:
[0006] S1. Preparation of a mixed paraffin wax forming agent: a plurality of paraffin waxes with different grades are mixed to prepare a mixed paraffin wax forming agent with gradient gasification dewaxing characteristics, wherein the mixed paraffin wax forming agent comprises at least two of paraffin wax with grade A, paraffin wax with grade B and paraffin wax with grade C;
[0007] S2, pre-grinding treatment: adding the mixed paraffin wax molding agent and the grinding balls into a ball mill for pre-grinding treatment to ensure that the mixed paraffin wax molding agent and the grinding balls are evenly mixed;
[0008] S3, ball milling and drying: adding a mixed material including WC powder, Co powder, ball milling medium and surfactant into the ball mill, and then spray drying to obtain a dry and uniform mixed material;
[0009] S4, pressing and molding: pressing and molding the dried and uniform mixture into a blade compact;
[0010] S5, gradient dewaxing treatment: placing the blade compact in a sintering furnace, and performing heat preservation treatment at multiple different temperature points by controlling the furnace temperature within the range of 150-500°C, so that paraffin wax of different grades is slowly removed from the core of the compact to the surface in sequence;
[0011] S6, sintering and cooling: after dewaxing is completed, the temperature is raised, sintered and cooled to obtain a cemented carbide sintered blank.
[0012] As a preferred embodiment of the method for improving the surface quality of cemented carbide sintered blanks described in the present invention, the amount of the mixed paraffin molding agent added is 0.5-3% of the weight of the mixed raw material.
[0013] As a preferred embodiment of the method for improving the surface quality of cemented carbide sintered blanks described in the present invention, the addition amounts of A-grade paraffin, B-grade paraffin and C-grade paraffin are X, Y and Z of the weight of the mixed raw materials, respectively, wherein X is 0.3-1.3%, Y is 0.5-1.7% and Z is 0.4-1.4%.
[0014] As a preferred embodiment of the method for improving the surface quality of cemented carbide sintered blanks described in the present invention, wherein: the A-grade paraffin is composed of one or more of the 40-50-grade paraffins, the B-grade paraffin is composed of one or more of the 52-60-grade paraffins, and the C-grade paraffin is composed of one or more of the 62-70-grade paraffins.
[0015] As a preferred embodiment of the method for improving the surface quality of cemented carbide sintered blanks described in the present invention, wherein: in the step S1, the mixing method of the mixed paraffin molding agent includes heating paraffins of different grades to liquid state respectively and then mixing them in proportion, or first mixing solid paraffins in proportion and then heating and melting them uniformly.
[0016] As a preferred embodiment of the method for improving the surface quality of cemented carbide sintered blanks described in the present invention, wherein: in the step S2, the pre-grinding time is 20 to 60 minutes.
[0017] As a preferred embodiment of the method for improving the surface quality of cemented carbide sintered blanks described in the present invention, wherein: in the step S3, the ball milling medium is alcohol.
[0018] As a preferred embodiment of the method for improving the surface quality of cemented carbide sintered blanks described in the present invention, wherein: in the step S3, the surfactant is one or more of oleic acid, stearic acid, octadecanoic acid, palmitic acid and ethyl desensitization.
[0019] As a preferred embodiment of the method for improving the surface quality of cemented carbide sintered blanks described in the present invention, wherein: in the step S5, under the condition of protective gas atmosphere, the environmental pressure is controlled to be 10-100 kPa, and a gradient dewaxing treatment is performed.
[0020] As a preferred embodiment of the method for improving the surface quality of cemented carbide sintered blanks described in the present invention, wherein: in the step S5, under the reducing atmosphere of H2 or CH4, the flow rate is controlled to be 10-200 L / min, and a gradient dewaxing treatment is performed.
[0021] As a preferred embodiment of the method for improving the surface quality of cemented carbide sintered blanks described in the present invention, wherein: in the step S5, the furnace temperature is heated to 150-250°C and kept warm for 30-120 minutes to remove the A-grade paraffin.
[0022] As a preferred embodiment of the method for improving the surface quality of cemented carbide sintered blanks described in the present invention, wherein: in the step S5, the furnace temperature is heated to 200-300°C and kept warm for 30-120 minutes to remove the B-grade paraffin.
[0023] As a preferred embodiment of the method for improving the surface quality of cemented carbide sintered blanks described in the present invention, wherein: in the step S5, the furnace temperature is heated to 250-350°C and kept warm for 30-120 minutes to remove C-grade paraffin.
[0024] As a preferred embodiment of the method for improving the surface quality of cemented carbide sintered blanks described in the present invention, wherein: in the step S6, the temperature is raised to 800-1200°C and sintered under vacuum conditions for 90-150 minutes, the temperature is raised to 1300-1550°C again and an inert protective gas is filled and pressure sintered for 30-45 minutes, then slowly cooled to 800-1200°C and kept warm for 60-90 minutes, and finally rapidly cooled to room temperature to obtain a cemented carbide sintered blank.
[0025] To solve the above technical problem, according to another aspect of the present invention, the present invention provides the following technical solution:
[0026] A cemented carbide sintered blank is prepared by adopting the above method for improving the surface quality of a cemented carbide sintered blank, and its surface roughness Sa is less than or equal to 400nm.
[0027] The beneficial effects of the present invention are as follows:
[0028] The present invention provides a method for improving the surface quality of cemented carbide sintered blanks, which effectively reduces the pore channels generated during the dewaxing process by introducing a mixed paraffin molding agent with gradient gasification dewaxing characteristics and combining an optimized dewaxing process, significantly improves the surface finish of the cemented carbide sintered blank, enhances the coating adhesion, reduces the cutting resistance, and improves the overall product quality. The surface roughness Sa of the cemented carbide sintered blank is ≤400nm. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0030] Figure 1 This is a surface picture of the cemented carbide sintered blank prepared in Example 1.
[0031] Figure 2 This is a surface picture of the cemented carbide sintered blank prepared in Comparative Example 1.
[0032] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0033] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] According to one aspect of the present invention, the present invention provides the following technical solution:
[0035] A method for improving the surface quality of a cemented carbide sintered blank comprises the following steps:
[0036] S1. Preparation of a mixed paraffin wax forming agent: a plurality of paraffin waxes with different grades are mixed to prepare a mixed paraffin wax forming agent with gradient gasification dewaxing characteristics, wherein the mixed paraffin wax forming agent comprises at least two of paraffin wax with grade A, paraffin wax with grade B and paraffin wax with grade C;
[0037] S2, pre-grinding treatment: adding the mixed paraffin wax molding agent and the grinding balls into a ball mill for pre-grinding treatment to ensure that the mixed paraffin wax molding agent and the grinding balls are evenly mixed;
[0038] S3, ball milling and drying: adding a mixed material including WC powder, Co powder, ball milling medium and surfactant into the ball mill, and then spray drying to obtain a dry and uniform mixed material;
[0039] S4, pressing and molding: pressing and molding the dried and uniform mixture into a blade compact;
[0040] S5, gradient dewaxing treatment: placing the blade compact in a sintering furnace, and performing heat preservation treatment at multiple different temperature points by controlling the furnace temperature within the range of 150-500°C, so that paraffin wax of different grades is slowly removed from the core of the compact to the surface in sequence;
[0041] S6, sintering and cooling: after dewaxing is completed, the temperature is raised, sintered and cooled to obtain a cemented carbide sintered blank.
[0042] Preferably, the amount of the mixed paraffin molding agent added is 0.5-3% by weight of the mixed raw material.
[0043] Preferably, the added amounts of paraffin wax A, paraffin wax B and paraffin wax C are X, Y and Z of the weight of the mixed raw materials, respectively, wherein X is 0.3-1.3%, Y is 0.5-1.7% and Z is 0.4-1.4%.
[0044] Preferably, the A-labeled paraffin wax is composed of one or more of the 40-50-labeled paraffin waxes, the B-labeled paraffin wax is composed of one or more of the 52-60-labeled paraffin waxes, and the C-labeled paraffin wax is composed of one or more of the 62-70-labeled paraffin waxes.
[0045] Preferably, in step S1, the mixing method of the mixed paraffin molding agent includes heating paraffins of different grades to liquid state respectively and then mixing them in proportion, or first mixing solid paraffins in proportion and then heating and melting them uniformly.
[0046] Preferably, in step S2, the pre-grinding time is 20 to 60 minutes.
[0047] Preferably, in step S3, the ball milling medium is alcohol; the surfactant is one or more of oleic acid, stearic acid, octadecanoic acid, palmitic acid and ethyl desensitization; the ball-to-material ratio is 4:1, and the ball milling time is 30-50 hours.
[0048] Preferably, in step S5, under the condition of nitrogen or argon protective gas atmosphere, the environmental pressure is controlled to be 10-100 kPa, and the gradient dewaxing treatment is performed.
[0049] Preferably, in step S5, under the reducing atmosphere of H2 or CH4, the flow rate is controlled to be 10-200 L / min, and a gradient dewaxing treatment is performed.
[0050] Preferably, in step S5, the furnace temperature is heated to 150-250° C. and kept warm for 30-120 min to remove the A-grade paraffin.
[0051] Preferably, in step S5, the furnace temperature is heated to 200-300° C. and kept warm for 30-120 min to remove the B-label paraffin.
[0052] Preferably, in step S5, the furnace temperature is heated to 250-350° C. and kept warm for 30-120 min to remove the C-labeled paraffin.
[0053] Preferably, in step S6, the temperature is raised to 800-1200°C and sintered under vacuum conditions for 90-150 minutes, the temperature is raised to 1300-1550°C again and an inert protective gas is filled and pressure sintered for 30-45 minutes, then slowly cooled to 800-1200°C and kept warm for 60-90 minutes, and finally rapidly cooled to room temperature to obtain a cemented carbide sintered blank.
[0054] According to another aspect of the present invention, the present invention provides the following technical solution:
[0055] A cemented carbide sintered blank is prepared by adopting the above method for improving the surface quality of a cemented carbide sintered blank, and its surface roughness Sa is less than or equal to 400nm.
[0056] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0057] Example 1
[0058] A method for improving the surface quality of cemented carbide sintered blanks, selecting the target grade YG10, the specific composition is: WC (Fischer particle size is 3μm) content is 90wt%, Co (Fischer particle size is 1.5μm) content is 10wt%. The amount of grinding medium alcohol added is 300mL / kg, the amount of surfactant oleic acid added is 0.5mL / kg, and the ingredients are prepared according to the selected grade to obtain a mixed raw material. The following steps are included:
[0059] S1. The paraffin wax of grade A is paraffin wax No. 46, which accounts for 1.2% of the weight of the mixed raw material; the paraffin wax of grade B is paraffin wax No. 60, which accounts for 1.2% of the weight of the mixed raw material. The two paraffins are mixed in solid state, heated and stirred to melt into liquid to obtain liquid mixed paraffin;
[0060] S2. Add the mixed paraffin and grinding balls into a ball mill and pre-grind for 30 minutes;
[0061] S3. Add the mixed material into the ball mill to ensure a ball-to-material ratio of 4:1, and ball mill for 40 hours. After ball milling, the mixed material is prepared by unloading and spraying.
[0062] S4. The mixture is pressed into a 5.25mm*6.5mm*20mm green compact;
[0063] S5. The compact is placed in a dewaxing and sintering integrated sintering furnace for sintering. Under a hydrogen atmosphere, the flow rate is controlled at 100L / min, the temperature is slowly raised to 200°C, kept for 100min, and then raised to 350°C, kept for 100min, and the dewaxing is completed;
[0064] S6. Continue to heat up to 1100℃ and sinter in vacuum for 90min, then heat up to 1450℃ and sinter under pressure with nitrogen protective gas for 40min, slowly cool to 900℃ and keep warm for 90min, then rapidly cool to room temperature and sinter into a blank.
[0065] Comparative Example 1
[0066] The difference from Example 1 is that in step S1, only 2.5% of the weight of the mixed material weight of paraffin No. 50 is used. In step S5, the compact is placed in a dewaxing and sintering integrated sintering furnace for sintering, and the temperature is slowly raised to 220° C. in a hydrogen atmosphere, and the temperature is kept for 120 minutes to complete the dewaxing.
[0067] The sintered blanks prepared in Example 1 and Comparative Example 1 were tested for blade surface roughness using an Alicona surface quality measuring instrument.
[0068] Table 1 The roughness results of Example 1 and Comparative Example 1 are as follows
[0069]
[0070] As can be seen from Table 1, after adding the mixed paraffin prepared by adding A-grade paraffin (No. 46) and B-grade paraffin (No. 60), the surface roughness Sa of the blade blank prepared by pressing and sintering the mixed material is significantly improved compared with the single No. 50 paraffin.
[0071] The surface picture of the cemented carbide sintered blank prepared in Example 1 is as follows Figure 1 As shown in the figure, after adding the mixed paraffin prepared by paraffin A (No. 46) and paraffin B (No. 60), the holes on the alloy surface are smaller and the surface is smoother. Figure 2 As shown in the figure, after adding a single paraffin wax No. 50, the alloy surface has more holes and the surface is "pitted". It can be seen that after adding a mixed paraffin wax prepared by adding multiple paraffin waxes of different grades, combined with a suitable dewaxing process, the surface quality of the cemented carbide sintered blank is significantly improved, the surface quality holes are reduced, and the surface is smoother.
[0072] Example 2
[0073] A method for improving the surface quality of cemented carbide sintered blanks, selecting the target grade YG6, the specific composition is: WC (Fischer particle size is 2μm) content is 94wt%, Co (Fischer particle size is 1.5μm) content is 6wt%. The amount of grinding medium alcohol added is 300mL / kg, the amount of surfactant oleic acid added is 0.5mL / kg, and the ingredients are prepared according to the selected grade to obtain a mixed raw material. The following steps are included:
[0074] S1. The paraffin wax of grade A is paraffin wax No. 48, and the amount thereof added is 0.6% by weight of the raw material of the mixture; the paraffin wax of grade B is paraffin wax No. 54, and the amount thereof added is 0.8% by weight of the raw material of the mixture; the paraffin wax of grade C is paraffin wax No. 62, and the amount thereof added is 0.6% by weight of the raw material of the mixture; the paraffin waxes are melted into liquid state respectively, and then stirred and mixed to obtain liquid mixed paraffin wax;
[0075] S2. Add the mixed paraffin and grinding balls into a ball mill and pre-grind for 30 minutes;
[0076] S3. Add the mixed material into the ball mill to ensure a ball-to-material ratio of 4:1, and ball mill for 50 hours. After ball milling, the mixed material is prepared by unloading and spraying.
[0077] S4. The mixture is pressed into a 5.25mm*6.5mm*20mm green compact;
[0078] S5. The compact is placed in a dewaxing sintering furnace and sintered under a nitrogen atmosphere, the pressure is maintained at 90 KPa, the temperature is slowly raised to 200 ° C, kept warm for 60 min, then raised to 250 ° C, kept warm for 60 min, and then raised to 300 ° C, kept warm for 60 min, to complete the dewaxing;
[0079] S6. Continue to heat up to 1100℃ and sinter in vacuum for 90min, then heat up to 1450℃ and sinter under pressure with nitrogen protective gas for 40min, slowly cool to 900℃ and keep warm for 90min, then rapidly cool to room temperature and sinter into a blank.
[0080] Comparative Example 2
[0081] The difference from Example 2 is that in step S1, only 2.5% of the weight of the mixed material weight of paraffin wax No. 56 is used. In step S5, the compact is placed in a dewaxing and sintering integrated sintering furnace for sintering, and the temperature is slowly raised to 250° C. in a hydrogen atmosphere and kept warm for 120 minutes to complete the dewaxing.
[0082] The sintered blanks prepared in Example 2 and Comparative Example 2 were tested for blade surface roughness using an Alicona surface quality measuring instrument.
[0083] Table 2 The roughness results of Example 2 and Comparative Example 2 are as follows
[0084]
[0085] As can be seen from Table 2, after adding the mixed paraffin prepared by paraffin A (No. 48), paraffin B (No. 54) and paraffin C (No. 60), the surface roughness Sa of the blade blank prepared by pressing and sintering the mixed material is significantly improved compared with the single No. 56 paraffin.
[0086] Example 3
[0087] A method for improving the surface quality of cemented carbide sintered blanks, selecting the target grade YG10, the specific composition is: WC (Fischer particle size is 3μm) content is 90wt%, Co (Fischer particle size is 1.5μm) content is 10wt%. The amount of grinding medium alcohol added is 300mL / kg, the amount of surfactant oleic acid added is 0.5mL / kg, and the ingredients are prepared according to the selected grade to obtain a mixed raw material. The following steps are included:
[0088] S1. The paraffin wax of grade A is paraffin wax No. 44, and its addition amount is 0.4% of the weight of the mixed raw material; the paraffin wax of grade B is paraffin wax No. 52 and paraffin wax No. 60, and its addition amount is 0.7% and 0.8% of the weight of the mixed raw material respectively; the paraffin wax of grade C is paraffin wax No. 66, and its addition amount is 0.5% of the weight of the mixed raw material. After mixing in the solid state, heat and stir to melt into liquid to obtain liquid mixed paraffin;
[0089] S2. Add the liquid paraffin mixture and grinding balls into a ball mill and pre-grind for 30 min;
[0090] S3. Add the mixed material into the ball mill to ensure a ball-to-material ratio of 4:1, and ball mill for 30 hours. After ball milling, the mixed material is prepared by unloading and spraying.
[0091] S4. The mixture is pressed into a 5.25mm*6.5mm*20mm green compact;
[0092] S5. The compact is placed in a dewaxing and sintering integrated sintering furnace for sintering. Under a hydrogen atmosphere, the flow rate is controlled at 100L / min, and the temperature is slowly raised to 160°C, kept warm for 40min, and then raised to 220°C, kept warm for 40min, and then raised to 280°C, kept warm for 40min, and then raised to 330°C, kept warm for 40min, and the dewaxing is completed;
[0093] S6. Continue to heat up to 1100℃ and sinter in vacuum for 90min, then heat up to 1450℃ and sinter under pressure with nitrogen protective gas for 40min, slowly cool to 900℃ and keep warm for 90min, then rapidly cool to room temperature and sinter into a blank.
[0094] Comparative Example 3
[0095] The difference from Example 3 is that in step S1, only 2.5% of the weight of the mixed material weight of No. 60 paraffin is used as paraffin. In step S5, the compact is placed in a dewaxing and sintering integrated sintering furnace for sintering, and the temperature is slowly raised to 300° C. in a hydrogen atmosphere, and the temperature is kept for 120 minutes to complete the dewaxing.
[0096] The sintered blanks prepared in Example 3 and Comparative Example 3 were tested for blade surface roughness using an Alicona surface quality measuring instrument.
[0097] Table 3 The roughness results of Example 3 and Comparative Example 3 are as follows
[0098]
[0099] As can be seen from Table 3, after adding the mixed paraffin prepared by A-grade paraffin (No. 44), B-grade paraffin (No. 52, No. 60) and C-grade paraffin (No. 66), the surface roughness Sa of the blade blank prepared by pressing and sintering the mixed material is significantly improved compared with the single No. 60 paraffin.
[0100] The present invention introduces a mixed paraffin molding agent with gradient gasification dewaxing characteristics and combines it with an optimized dewaxing process to effectively reduce the pore channels generated during the dewaxing process, significantly improve the surface finish of the cemented carbide sintered blank, enhance the coating adhesion, reduce the cutting resistance, and improve the overall product quality. The surface roughness Sa of the cemented carbide sintered blank is ≤400nm.
[0101] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for improving the surface finish of a cemented carbide sintered blank, characterized in that: The steps include: S1. Preparation of mixed paraffin wax forming agent: a plurality of paraffin waxes with different grades are selected and mixed to prepare a mixed paraffin wax forming agent with gradient gasification dewaxing characteristics, wherein the mixed paraffin wax forming agent is at least two of paraffin waxes with grades A, B and C; paraffin wax with grades A is composed of one or more paraffin waxes with grades 40 to 50, paraffin wax with grades B is composed of one or more paraffin waxes with grades 52 to 60, and paraffin wax with grades C is composed of one or more paraffin waxes with grades 62 to 70; the amount of the mixed paraffin wax forming agent added is 0.5 to 3% of the weight of the mixed raw material; the amounts of paraffin wax with grades A, paraffin wax with grades B and paraffin wax with grades C are X, Y and Z of the weight of the mixed raw material, respectively, wherein X is 0.3 to 1.3%, Y is 0.5 to 1.7% and Z is 0.4 to 1.4%; S2, pre-grinding treatment: adding the mixed paraffin wax molding agent and the grinding balls into a ball mill for pre-grinding treatment to ensure that the mixed paraffin wax molding agent and the grinding balls are evenly mixed; S3, ball milling and drying: adding a mixed material including WC powder, Co powder, ball milling medium and surfactant into the ball mill, and then spray drying to obtain a dry and uniform mixed material; S4, pressing and molding: pressing and molding the dried and uniform mixture into a blade compact; S5, gradient dewaxing treatment: placing the blade compact in a sintering furnace, and performing heat preservation treatment at multiple different temperature points within the range of 150-500°C by controlling the furnace temperature, so that different grades of paraffin wax are slowly removed from the core of the compact to the surface in sequence; heating the furnace temperature to 150-250°C and keeping it warm for 30-120 minutes to remove the A grade paraffin wax; heating the furnace temperature to 200-300°C and keeping it warm for 30-120 minutes to remove the B grade paraffin wax; heating the furnace temperature to 250-350°C and keeping it warm for 30-120 minutes to remove the C grade paraffin wax; S6, sintering and cooling: after dewaxing is completed, the temperature is raised, sintered and cooled to obtain a cemented carbide sintered blank, and the surface roughness of the cemented carbide sintered blank Sa≤400nm.
2. The method for improving the surface finish of cemented carbide sintered blank according to claim 1, characterized in that: In the step S1, the mixing method of the mixed paraffin molding agent includes heating paraffins of different grades to liquid state respectively and then mixing them in proportion, or first mixing solid paraffins in proportion and then heating and melting them uniformly.
3. The method for improving the surface finish of cemented carbide sintered blank according to claim 1, characterized in that: In step S3, the surfactant is one or more of oleic acid, stearic acid, octadecanoic acid, and palmitic acid.
4. The method for improving the surface finish of cemented carbide sintered blank according to claim 1, characterized in that: In the step S5, under the protective gas atmosphere, the environmental pressure is controlled to be 10-100 kPa, and a gradient dewaxing treatment is performed.
5. The method for improving the surface finish of cemented carbide sintered blank according to claim 1, characterized in that: In the step S5, under the reducing atmosphere of H2 or CH4, the flow rate is controlled to be 10-200 L / min to perform gradient dewaxing treatment.
6. The method for improving the surface finish of cemented carbide sintered blank according to claim 1, characterized in that: In the step S6, the temperature is raised to 800-1200° C. and sintered under vacuum conditions for 90-150 minutes, the temperature is raised to 1300-1550° C. again and an inert protective gas is filled and pressure sintered for 30-45 minutes, then slowly cooled to 800-1200° C. and kept warm for 60-90 minutes, and finally rapidly cooled to room temperature to obtain a cemented carbide sintered blank.
7. A cemented carbide sintered blank, characterized in that: The hard alloy sintered blank is prepared by the method for improving the surface finish of the hard alloy sintered blank according to any one of claims 1 to 6.
Citation Information
Patent Citations
Dewaxing and sintering integrated technique for large product of hard alloy
CN101343697A
Hard alloy extrusion molding agent based on paraffin base and extrusion feeding preparing process thereof
CN111468735A
Forming agent for hard alloy extrusion bar billet and mixing process thereof
CN111940720A